Relationship between ice hockey-specific complex test and maximal strength, aerobic capacity and postural regulation in professional players - Schwesig, R.; Hermassi, S.; Edelmann, S.; Thorhauer, U.; Schulze, S.; Fieseler, G.; Delank, K. S.; Shephard, R. J.; Chelly, M. S. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: We aimed to examine the validity of an ice hockey-specific complex test (IHCT) and nonspecific off-ice tests for sports performance.